The hero in contemporary revolutionary and military literature: a typology of characters - Kulinska, Yanina; Gerasimenko, Nina; Koval, Olena; Kvitsynska, Viktoriia (Linguistics and Culture Review, 2021)
The relevance of the issue stems from the urgent need to analyse with the help of the latest methods the new phenomena of modern Ukrainian literature, in particular the block of its revolutionary and military prose as one of the directions of modern literature. The aim of the work is to develop and thoroughly analyse the works of 2014-2020 dedicated to the Revolution of Dignity and the war in Eastern Ukraine, to study their genre nature, to clarify their characteristic features and to create a new typology of the modern literary hero. Among the main methods for processing diary texts were historical-biographical, comparative historical, comparative, structural-narratological, interdisciplinary, as well as elements of hermeneutical, intertextual methods, text and discourse analysis, etc. The paper provides a detailed analysis and proposes a new typology of the modern literary hero. The materials of the study can be used to prepare basic and special courses on the theory of literature, the history of Ukrainian and foreign literature, while working on manuals and textbooks, including those for higher education institutions, etc.